Odpowiedź :
Cześć!
Obliczenia
[tex]3\frac{1}{2}-2\frac{3}{4}=3\frac{1\cdot2}{2\cdot2}-2\frac{3}{4}=3\frac{2}{4}-2\frac{3}{4}=2\frac{4+2}{4}-2\frac{3}{4}=2\frac{6}{4}-2\frac{3}{4}=\frac{3}{4}\\\\1\frac{2}{3}-\frac{5}{6}=1\frac{2\cdot2}{3\cdot2}-\frac{5}{6}=1\frac{4}{6}-\frac{5}{6}=\frac{1\cdot6+4}{6}-\frac{5}{6}=\frac{6+4}{6}-\frac{5}{6}=\frac{10}{6}-\frac{5}{6}=\frac{5}{6}[/tex]
Odpowiedź:
[tex]3\frac{1}{2}-2\frac{3}{4} = 3,50-2,75=\boxed{0,75} }(\frac{3}{4} )\\\\1\frac{2}{3} - \frac{5}{6}=\frac{5}{3}-\frac{5}{6}=\boxed{\frac{5}{6} }[/tex]
Szczegółowe wyjaśnienie: